The Effect of Teaching according to the Bybee Constructive Learning Model on the Acquisition of Secondary School Students of Concepts of Islamic Education in Jordan - Ashraah, Mamduh M.; Mustafa, Amani Sharif (Dirasat: Educational Sciences, 2021)
The study aims to investigate the effect of teaching according to the Bybe model of constructivist learning on the acquisition of Islamic education concepts by secondary school students. The study sample consisted of (72) female students from a secondary school for females in Zarqa. The students were assigned to an experimental group (n=38) which was taught using the Bybe model and a control group (n=38) which was taught in the usual way. The model was applied to two units of the Islamic Education textbook for the first scientific secondary grade. The results showed the existence of alternative perceptions among female secondary school students and that the questions related to the unit of Islamic jurisprudence obtained the highest percentages of alternative perceptions. The results also showed a statistically significant effect attributed to teaching method in favor of the experimental group. The study concluded with a number of recommendations, including the need to train Islamic education teachers on appropriate teaching strategies according to the Bybee model.